Exploratory studies on effects of growth location and conditioning on treatability and permeability of southern pine lumber - Winandy, Jerrold E.; Barnes, H. M.; Morrell, Jeffrey J. (Maderas. Ciencia y Tecnología, 2022)
Southern pine lumber is often treated with preservatives, but issues related to initial kiln-drying conditions and geographic source across the wide southern pine growth range have been suspected to negatively affect subsequent permeability and treatability. These effects remain poorly understood. In this series of exploratory studies, southern pine from across part of the growing range subjected to different kiln-drying regimes was evaluated in three phases exploring the effects of geographic source and initial kiln-drying conditions on permeability, pit structure and eventual preservative treatment of southern pine lumber. The results suggest that elevated temperatures coupled with poor humidity control at the start of the kiln drying process may negatively influence permeability and preservative penetration, but had only negligible effects on several other wood properties.